2004
DOI: 10.1890/02-5296
|View full text |Cite
|
Sign up to set email alerts
|

Semiarid Old‐field Restoration: Is Neighbor Control Needed?

Abstract: Restoration practice suggests that neighbor control is essential in semiarid grasslands, but ecological theory predicts that neighbor effects are relatively small in young fields. We investigated the effectiveness of neighbor control (mowing and herbicide) for establishing native grasses in a recently abandoned field in southwestern Saskatchewan, Canada. We also examined its interactions with common restoration techniques, such as mulching (straw and sawdust) and contrasting sowing methods (drilling, and broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
(47 reference statements)
1
39
0
Order By: Relevance
“…These year-to-year differences in cover of native forbs reinforce the importance of yearly variation in structuring these communities (Wilson et al 2004;Cox and Allen 2008). Seeded species were also affected by yearly variation, and some, especially the perennials, may not have established during the short timespan (2 years) of the study due to the relatively late seeding and yearly variations in timing and amounts of precipitation.…”
Section: Discussionmentioning
confidence: 70%
“…These year-to-year differences in cover of native forbs reinforce the importance of yearly variation in structuring these communities (Wilson et al 2004;Cox and Allen 2008). Seeded species were also affected by yearly variation, and some, especially the perennials, may not have established during the short timespan (2 years) of the study due to the relatively late seeding and yearly variations in timing and amounts of precipitation.…”
Section: Discussionmentioning
confidence: 70%
“…Treatment effects on native grasses declined although native cover remained lower in the control, soil removal, and herbicide plots that were unmulched. Other studies have suggested that interannual climatic variation, which is beyond the control of practitioners, may be more important than the restoration method used (Cox and Allen 2011;Wilson et al 2004), so that investing resources in multiple years of seeding or planting may enhance restoration success more than expensive efforts to control exotic competition. What is clear is that long-term monitoring is needed to evaluate the efficacy of different restoration treatments, a call that has been made repeatedly in the academic literature (Matthews and Spyreas 2010;Rinella et al 2012), but is less commonly implemented (Kettenring and Adams 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Historical and stochastic effects create patterns not fully explicable with simple deterministic models. Several types of contingency are critical drivers of community structure in ecological systems, and are not only theoretically interesting, but also have strong implications for ecological restoration (Bakker et al 2003;Wilson et al 2004). For example, the presence or absence of herbivores can have profound effects on community development and structure (see Howe & Lane 2004).…”
Section: O N T I N G E N C Y a N D Y E A R E F F E C T Smentioning
confidence: 99%